Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian Melalui Minat Beli Pada Platfrom Tiktok Shop - Mutiara, Mirsatya; Mira Kartika Dewi Djunaedi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The growth of social media drives the progress of digital business in Indonesia today, where there is an online shopping platform that has become a habit in making purchases of products online. This study aims to determine the effect of service quality and product quality on purchasing decisions through purchase interest as an intervening variable. This study used 100 respondents who had purchased products on the TikTok shop platform, by distributing questionnaires online. The data analysis of this study used SEM-PLS. The findings of this study indicate that service quality and product quality positively influence purchase interest, purchase interest on purchasing decisions has a positive influence, service quality and product quality on purchasing decisions have a positive influence, service quality and product quality on purchasing decisions through purchase interest have a positive influence.